Curcumin ameliorates streptozotocin-induced liver damage through modulation of endoplasmic reticulum stress-mediated apoptosis in diabetic rats. (March 2015) - Afrin, R.; Arumugam, S.; Soetikno, V.; Thandavarayan, R. A.; Pitchaimani, V.; Karuppagounder, V.; Sreedhar, R.; Harima, M.; Suzuki, H.; Miyashita, S.; Nomoto, M.; Suzuki, K.; et al.
Abstract: We investigated the effect of curcumin on liver injury in diabetic rats induced by streptozotocin (STZ) through modulation of endoplasmic reticulum stress (ERS) and unfolded protein response (UPR). Experimental diabetes was induced by a single intraperitoneal injection of STZ (55 mg/kg), and curcumin was given at 100 mg/kg by gavage for 56 days. We observed that curcumin improved the morphological and histopathological changes, significantly decreased hepatic ERS marker protein: glucose-regulated protein 78, and improved liver function in diabetic rats. Moreover, treatment with curcumin markedly decreased the sub-arm of the UPR signaling protein such as phospho–double-stranded RNA-dependent protein kinase-like ER kinase, CCAAT/enhancer-binding protein homologous protein, tumor necrosis factor receptor-associated factor 2, and inositol-requiring enzyme1α; and inhibited tumor necrosis factor α, interleukin 1β, phospho-p38 mitogen-activated protein kinase, and apoptosis signal-regulating kinase 1 in liver tissues of diabetic rats. Apoptotic and anti-apoptotic signaling proteins, such as cleaved caspase-3 and B-cell lymphoma 2, were significantly increased and decreased, respectively in diabetic rats; curcumin treatment prevented all of these alterations. In summary, our results indicate that curcumin has the potential to protect the diabetic liver by modulating hepatic ERS-mediated apoptosis, and provides a novel therapeutic strategy for the diabetic liver damage.